The lessons of tragedy : statecraft and world order - Brands, Hal, 1983-; Edel, Charles N., 1979- (New Haven : Yale University Press, 2019)
The ancient Greeks hard-wired a tragic sensibility into their culture. By looking disaster squarely in the face, by understanding just how badly things could spiral out of control, they sought to create a communal sense of responsibility and courage--to spur citizens and their leaders to take the difficult actions necessary to avert such a fate. Today, after more than seventy years of great-power peace and a quarter-century of unrivaled global leadership, Americans have lost their sense of tragedy. They have forgotten that the descent into violence and war has been all too common throughout human history. This amnesia has become most pronounced just as Americans and the global order they created are coming under graver threat than at any time in decades. In a forceful argument that brims with historical sensibility and policy insights, two distinguished historians argue that a tragic sensibility is necessary if America and its allies are to address the dangers that menace the international order today. Tragedy may be commonplace, Brands and Edel argue, but it is not inevitable-so long as we regain an appreciation of the world's tragic nature before it is too late.
The virtues of tragdy -- Tragedy as the norm -- Tragedy as inspiration -- The great escape -- The contemporary amnesia -- The darkening horizon -- Rediscovering tragedy.
Sisältää bibliografisia viitteitä (sivut 167-191) ja hakemiston.
Keywords: International relations; Diplomatic relations; International relations; United States -- Foreign relations; United States